The effects of exergames on emotional well-being of older adults. (September 2020) - Zheng, Han; Li, Jinhui; Salmon, Charles T.; Theng, Yin-Leng
Abstract: Exergames have been adopted as a new approach to promote healthy and active aging in recent years. This study aimed to understand the effects of exergames on emotional well-being (positive and negative affects) of older adults and further explore factors influencing the two types of affects after playing exergames. The study used a 2 (pre-test vs. post-test) × 3 (play alone vs. play with peers vs. play with youths) mixed factorial design with 319 Singaporean older adults with an average age of 73 years old over six weeks. Results of this study showed that playing exergames could lead to an increase in positive affect (Mdifference = 0.33, p < .001) and a decrease in negative affect (Mdifference = −0.19, p < .001) over time. Additionally, while there was no significant difference across play groups in changing positive affect over time, participants who played alone showed a greater decline in negative affect compared to those playing with peers and those playing with youths. Further, we found that after playing exergames for six weeks, attitude toward exergames is related to two types of affects and sociability can mediate such relationships. Lastly, implications and limitations of this study are discussed. Highlights: A 2 × 3 experiment with 319 Singaporean older adults over 6 weeks Playing exergames increase positive affect and decrease negative affect over time Playing exergames alone has greater decline in negative affect than playing with peers or youth Sociability fully mediate the relationships between attitude and two types of emotions